2009
DOI: 10.1093/sleep/32.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Napping, Post-Lunch Dip, and Other Variations in Human Sleep Propensity

Abstract: SP can be modeled as a continuous variable, based on the multiplicative interaction of 2 basic sleep drives. The model predictions are in agreement with known variations of SP across 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 40 publications
3
37
1
Order By: Relevance
“…Lavie P. and Dement W.C. showed that insufficient sleep increases daytime sleepiness 8,33) . In addition, Bes F. et al reported that sleep propensity increases slightly and reaches its highest value in the early afternoon, at 2 P.M 34) . We suggest that daytime sleepiness at 2 P.M is the outcome most susceptible to improvement of night sleep.…”
Section: Discussionmentioning
confidence: 98%
“…Lavie P. and Dement W.C. showed that insufficient sleep increases daytime sleepiness 8,33) . In addition, Bes F. et al reported that sleep propensity increases slightly and reaches its highest value in the early afternoon, at 2 P.M 34) . We suggest that daytime sleepiness at 2 P.M is the outcome most susceptible to improvement of night sleep.…”
Section: Discussionmentioning
confidence: 98%
“…93 Participants can also be questioned about their levels of tiredness and quality of sleep the preceding evening to gain some information regarding the potential presence of sleep deprivation effects.…”
Section: Sleepmentioning
confidence: 99%
“…An explicit non-linear approach has been proposed with a multiplicative interaction, which successfully models the four main characteristics of sleep propensity across 24 h [276]. …”
Section: Pharmaco-sleep Study-related Topicsmentioning
confidence: 99%